Dampak Pelaksanaan UKGS oleh Guru Olahraga pada Karies Gigi di SD Inpres Unggulan BTN Pemda - Saleh, Muhammad; Angki, Johnny; Asriawal; Putri, Alimah (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2025)
One way to overcome dental and oral health problems in elementary school children is to involve government programs, namely the School Dental Health Business Program (UKGS) in every elementary school. This study aims to explore the role of sports teachers in the implementation of UKGS and its impact on the incidence of dental caries. This research uses quantitative and qualitative approaches. Data was collected through def-t and DMF-T examinations to assess the status of dental caries in students, as well as closed interviews with sports teachers to understand their role in implementing UKGS. The research sample consisted of 66 grade 5 students and sports teachers. The main aim of the research is to identify the role of sports teachers in implementing UKGS and to determine the dental caries status of students. The examination results indicated that the dental caries status of grade 5 students was in the very low category. Sports teachers in the UKGS program act as educators, motivators and facilitators in managing dental caries status in schools, which contributes to achieving effective implementation of the UKGS program. It is hoped that good implementation of the UKGS program can reduce the risk of dental caries in students, thereby reducing the level of dental caries in children at school.  Keywords: Sports teacher; UKGS; dental caries